Comparison of aluminum mordanted and nonmordanted wool yarns naturally dyed with Kansas black walnut, Osage orange, and eastern redcedar sawdust - Doty, Kelsie (Kansas State University, 2015)
This study compared the colorfastness of potassium aluminum sulfate (PAS) mordanted and nonmordanted 30/2 wool yarn, dyed with black walnut (Juglans Nigra), Osage orange (Maclura pomifera), and eastern redcedar (Juniperus virginiana) sawdust. Information from this study is intended to inform natural dye artisans and to increase the profitability of sawdust for farmers, ranchers, and mill owners who would otherwise find little use for this byproduct of timber manufacturing. Pre-testing ensured dyeings of visually comparable color depth and dye concentrations were pre-tested to find a standard depth of shade between the same dye on PAS mordanted and nonmordanted wool yarns. Tests for colorfastness to light, laundering and staining were performed in accordance to AATCC test methods. Resulting colors for exposed and unexposed specimens were rated using CIE L* a* b* values and AATCC gray scale for color change. GLM Anovas and two-sample t-tests were used to statistically analyze CIE L* a* b* values. As expected, findings indicated that dye absorption was improved with the use of a PAS mordant, especially for black walnut and eastern redcedar. For yarns premordanted with PAS the dyewoods became yellower. A PAS mordant slightly improved colorfastness to light for black walnut and eastern redcedar, but did not influence Osage orange which had an unexpected color change from bright yellow to warm brown after exposure to light. Colorfastness to laundering was slightly improved with PAS for Osage orange, while black walnut and eastern red cedar had slightly less color change without the mordant. This research was supported by the Agricultural Research Experiment Station and Kansas State University.
Keywords: Natural dyes; Mordant; Tannin; Black walnut; Osage orange; Eastern redcedar; Environmental Sciences (0768); Forestry (0478); Wood Sciences (0746)